Effect of genotype on the in vitro regeneration of Stevia rebaudiana via somatic embryogenesis (2016)
ABSTRACT: Stevia rebaudiana (Asteraceae) is a plant of economic importance because of its medicinal properties and the presence of sweetener compounds on its leaves. These compounds can be a substitute for sucrose in a wide variety of products used by persons with diabetes and obesity problems. To standardize an efficient and effective propagation method for the different Stevia genotypes grown in Colombia, this study evaluated the effect of different combinations of the plant growth regulators 2,4-dichlorophenoxyacetic acid (2,4-D), indole-3-acetic acid (IAA), indole-3-butyric acid (IBA), 6-(gamma, gamma-dimethylallylamino) purine (2iP) and Zeatin on the induction and development of somatic embryos. Adenine and coconut water were also evaluated as supplements in the basal culture medium Murashige and Skoog Basal Salt Mixture (MS) with glutamine. The combination of 2,4-D (18.09 μM) and 2iP (7.38 μM) produced the highest number of somatic embryos per explant, which had well-defined characteristics. The genotype showed a significant effect on the embryogenic response. In the “SRQ-93” genotype, the formation and development of somatic embryos was achieved, whereas the genotypes “Bertoni” and “Morita II” only yielded embryogenic and non-embryogenic calli, respectively. The conversion to seedlings was achieved on the regeneration medium containing gibberellic acid (GA3) (0.29 μM) and activated charcoal.